Archdeacons and the Law. (12th February 2019) - Steen, Jane
Abstract : Previous studies of archdeacons in this Journal defended their pastoral hearts in a ministry dominated by law. This article sees the archdeacon's pastoral and priestly ministry as created and enabled by law. It looks at the canonical description of the archdeacon's office before turning to the work of an archdeacon in such areas as visitations, parish and diocesan governance, faculty jurisdiction, care and discipline of clergy, conflict resolution and creative innovation. The article draws on relevant legislative instruments, including Acts, Measures and Codes of Practice; on case law; and on quasi-legislation such as diocesan handbooks. Its conclusions are based not only upon what is set down in these, but also upon what archdeacons actually do. Archdeacons across the Church of England and the Church in Wales, and a Channel Islands dean, responded to a short survey looking at archdeacons' work in relation to the stipulations of the law. The article concludes that archdeacons occupy a pivotal position in dioceses, both because of what the law requires and because of what it does not prohibit. They play a key role in shaping the church and its ministry. With bishops and others, they delight in its beauty and rejoice in its well-being.